THERMODYNAMIC DESCRIPTION OF EQUILIBRIA IN MIXED FLUIDS (H2O-NONPOLAR GAS) IN A WIDE RANGE OF TEMPERATURES (25-700°C) AND PRESSURES (1-5000 BAR) - Akinfiev N.N.; Zotov A.V. (My University, 2006)
A new method is proposed for calculating equilibria in mixed multicomponent systems H2O-nonpolar gas at high temperatures and pressures. The method is based on calculation of electrostatic interactions between a solute component and surrounding molecules of a solvent (H2O). The SUPCRT98 database and the Helgeson-Kirkham-Flowers equation of state for components of an aqueous solution were used for computer realization of the method. The thermodynamic properties of solute gases at elevated temperatures and pressures are calculated by the Redlich-Kwong equation. The dielectric properties of a mixed solvent are determined using the modified Kirkwood equation. The proposed method was approved in description of the available set of experimental data on constants of H2O and NaCl dissociation, as well as data on solubility of both covalent and ionic crystals [SiO2, AgCl, Ag2SO4, Ca(OH)2, CaCO3] in mixed solvents H2O-nonpolar component [1,4-dioxane (C4H4O2), Ar, CO2]. The calculation and experimental data agree in a wide range of PTx conditions (temperatures up to 500°C, pressures up to 5000 bar, and mole fractions (x) of a nonpolar component in fluid up to 0.3). The proposed approach can be used for assessing the Born parameters of solute components. The calculation algorithm developed allows us not only to consider separate reactions but also to study equilibria in hydrothermal systems as a whole. Hence, the proposed approach can be used for constructing thermodynamic models of evolution of fluids rich in volatile components and vital to natural processes of mineral formation. © Pleiades Publishing, Inc., 2006.